Toned Tummies and Bloated Bellies: Activia Yogurt and Gendered Digestion - Contois, Emily (Cuizine, 2014)
Populating grocery store aisles with its easily recognizable green containers, Activia (a probiotic yogurt) claims to help regulate the digestive system in fourteen days. The commercial success of this functional food product reveals intersections among discourses of digestion, gendered eating, ideal bodies, nutrition, health, and food pharmaceuticals, as eaters navigate an increasingly medicalized foodscape. This paper draws from print and online advertisements, product packaging, press coverage, and industry reports, as well as a variety of secondary sources that analyze digestion as a cultural act. From the naked, flat stomachs prominently featured in advertisements to the heart-shaped icons used to navigate its website, this paper also demonstrates how Activia constructs digestion and freedom from constipation as components of an idealized, white, middle to upper class, female identity.